Peningkatan Pengetahuan Ibu Nifas Tentang Penyebab dan Risiko Keputihan Patologis Melalui Media Komunikasi Digital di Klinik Permata Bunda Tahun 2025 - Adista, Nuria Fitri; Muslihah, Liana; Sari, Siva Septiana (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Pathological vaginal discharge in postpartum women is a reproductive health issue that is often overlooked but may lead to serious complications such as endometritis. Digital-based education provides an innovative approach to improve postpartum women’s knowledge regarding prevention and risks of pathological discharge. This community service program was conducted at Permata Bunda Clinic, Serang City, in 2025 involving postpartum mothers as participants. The method applied was health education through digital communication media including animated videos, infographics, and interactive educational messages delivered via WhatsApp Group. Evaluation was carried out using pretest and posttest. The results showed a significant improvement in participants’ knowledge, with the percentage of correct answers increasing from 40% in the pretest to 76% in the posttest, and the average score rising from 4.0 to 7.6. This demonstrates that digital communication media is effective in enhancing reproductive health knowledge. Moreover, this educational approach is consistent with Islamic values that emphasize personal hygiene and disease prevention. Therefore, this program provides a real contribution to improving postpartum women’s health and can serve as a model for developing digital-based health education in primary healthcare facilities.